Procedure, reading and interpretation of capsule endoscopy - Costa, Valeria Atenea (2024)
The capsule endoscopy (CE) is a minimally invasive diagnostic imaging technique, consisting of a disposable capsule that travels through the digestive system, transmitting images to a data recorder. CE has emerged as a tool for exploring the small intestine, however, the lack of standardization in interpretation and terminology has been a challenge in the medical community. This article proposes guidelines for the performance, reading, and interpretation of CE, highlighting its utility in various indications.